Portable micromanipulator for extreme climatic conditions. Issue 1 (July 2020) - Timofeev, A N; Berro, S M
Abstract: The problem of compensating for the partial loss of micromovements capabilities of a person in severe climatic conditions of the Arctic is studied. A portable manipulation system that reproduces the natural biomechanics of the human hand is proposed. The methods of manipulator control are analyzed. Promising areas of application of such systems for the repair of hard-to-reach equipment are considered.